Application of scoby bacterial cellulose as hydrocolloids on physicochemical, textural and sensory characteristics of mango jam - Chong, Ann Qi; Chin, Nyuk Ling; A. Talib, Rosnita; Kadir Basha, Roseliza (John Wiley and Sons, 2024)
BACKGROUND: The scoby pellicle of symbiotic culture of bacteria and yeast is a by-product from kombucha fermentation. While a portion is used as starter culture, the remainder is often discarded, yet it can be a valuable source of bacterial cellulose. RESULTS: Scoby from black, green and oolong tea kombucha fermentation was assessed for its hydrocolloid effects in mango jam-making through evaluation of physicochemical, textural and sensory characteristics. Quality of jam was significantly improved with water activity reduction up to 22.22% to 0.679, moisture content reduction up to 37.06% to 19.92%, and a pH drop up to 5.9% to 3.19 with the use of 20 to 100 g kg−1 scoby. In colour analysis, presence of scoby led to a brighter jam due to higher (Formula presented.) values from 30.98 to a range of 31.82 to 40.83. Texture of jam with scoby gave higher gel strength and adhesiveness, with the most prominent effects from the black tea kombucha. Overall acceptability in sensory test scoring was above 70% on a nine-point hedonic scale with the 40 g kg−1 green tea kombucha scoby jam chosen as the most preferred. CONCLUSION: Scoby gave significant contributions to jam stability, appearance and texture, showing potential as a clean-label food ingredient.